Iran's economic considerations after the war and its role in renewing of Iran-Saudi diplomatic relations - Amiri, Reza Ekhtiari; Ku Samsu, Ku Hasnita; Fereidouni, Hassan Gholipour (Canadian Academy of Oriental and Occidental Culture, 2010)
Iran-Saudi relationship has constantly been frictional after Islamic revolution of Iran. In general, Saudi heavy support of Iraqi government during Iran-Iraq war and Iran's holding political demonstration so-called the Liberation from Infidels gave rise to frigidity of mutual relations of the two countries. Meanwhile, one of the means that Saudi Arabia, as ally of Iraq, applied to put Iran under pressure was oil and reduction of its price in order to decrease Iran's foreign exchange revenues in which it could not supply its essential armaments. The problems, finally, led to cutting off Iran-Saudi bilateral relations in 1988. However, after termination of the war and in the early years of 1990s, Iran's relations with Persian Gulf countries in particular Saudi Arabia improved gradually. The present article hypothesizes that Iran's internal economic necessities such as reconstruction of the war-torn areas, improvement of economic situation and also public demands for better life in 1980s, mainly resulted from Iran-Iraq eight-year war, in one hand and its dependency on oil revenues to change the terrible situation on the other hand caused Iran to re-conciliate its relations with Saudi Arabia due to its influence on oil price and quota within OPEC. The study concludes that Iran's reliance on petrodollars and its endeavor to increase oil revenues as well as regaining its previous leadership in OPEC led to renewing of diplomatic relations with Saudi Arabia in 1991 and also their cooperation within the organization afterward.